VD_FINDINFO Décision / 2011 / 139 vom 21. Februar 2011 - VD Tribunal cantonal (2011)
CLASSEMENT DE LA PROCÉDURE, HONNEUR, INFRACTIONS CONTRE L'HONNEUR | 310 CPP (CH), 393 al. 1 let. a CPP (CH), 393 CPP (CH)